A Sea of Gamba: Making Environmental Harm Illegible in Northern Australia. (2nd October 2019) - Neale, Timothy
ABSTRACT: Science and Technology Studies (STS) scholarship has often been suspicious of the role of scientific knowledge and scientists in environmental governance, notably through paying critical attention to the workings of calculative rationalities and techniques. However, recent reforms within certain extractivist regions and nations such as the United States of America and Australia suggest that calculative management and the environmental data on which it is based is no longer a given. Arguably, the politics of rendering the ecologies around us legible through measures and values has changed. This is apparent by examining the case of Gamba grass ( Andropogon gayanus ), an invasive and fire-promoting 'weed' which is threatening the lives and futures of humans and nonhumans alike in Australia's Northern Territory. After becoming a target of environmental regulation in 2008, the plant has continued to thrive and expand its reach. Interviews and fieldwork with a range of practitioners engaged in bushfire and weed management show that there are many challenges to interceding in forms of environmental harm when we are governed by a politics of environmental illegibility. Pragmatic empirical engagements by STS scholars and others are necessary if these intercessions are to succeed.